2015
DOI: 10.1002/ajmg.a.36914
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplastic left heart syndrome and 21q22.3 deletion

Abstract: Hypoplastic left heart syndrome (HLHS) is a rare congenital heart defect (CHD), associated with extracardiac anomalies in the 15-28% of cases, in the setting of chromosomal anomalies, mendelian disorders, and organ defects. We report on a syndromic female newborn with HLHS and terminal 21q22.3 deletion (del 21q22.3), investigated by Fluorescence In Situ Hybridization (FISH) using a panel of 26 contiguous BAC probes. Although rare, del 21q22.3 has been described in two additional patients with HLHS. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…We found that 33% of our initial cases were not isolated, with chromosomal abnormalities found in 9%. LV obstruction is one of the most common congenital heart diseases with a strong genetic basis, and our numbers are in line with those previously reported for a 4% to 9% risk for aneuploidy . Regarding FAV, we had a successful technical procedure in all patients as compared with 80% reported, with two cases (22%) with intraoperative bradycardia, one of which responded to resuscitation.…”
Section: Discussionsupporting
confidence: 89%
“…We found that 33% of our initial cases were not isolated, with chromosomal abnormalities found in 9%. LV obstruction is one of the most common congenital heart diseases with a strong genetic basis, and our numbers are in line with those previously reported for a 4% to 9% risk for aneuploidy . Regarding FAV, we had a successful technical procedure in all patients as compared with 80% reported, with two cases (22%) with intraoperative bradycardia, one of which responded to resuscitation.…”
Section: Discussionsupporting
confidence: 89%
“…21q22 deletions have been reported in patients showing a wide phenotypic spectrum, including midline defects (frontonasal dysplasia, encephalocele, and corpus callosum agenesis) and learning disability [11]; syndromic hypoplastic left heart [12]; and MCA/ID including microcephaly and ocular coloboma [13]. Thus, it is difficult to evaluate the effect of the 21q partial monosomy on the clinical phenotype observed in the patients here reported.…”
Section: Discussionmentioning
confidence: 86%
“…Partial deletion of chromosome 21q is a rare chromosomal disorder with heterogeneous phenotype because of unique breakpoint and genetic background [32]. Clinical manifestations of 21q22.3 deletion individuals varied from mild, moderate, severe to lethal depending on the deleted region and concordant chromosomal aberrations [17,19,20]. We present phenotypes of a new case and 7 previously reported cases with 21q22.3 deletion.…”
Section: Discussionmentioning
confidence: 96%
“…We present phenotypes of a new case and 7 previously reported cases with 21q22.3 deletion. Except for 1 deceased newborn, all of them (7/7) had intellectual disability [20]. Four cases (4/6) had congenital cardiac defects, 2 of which were severe type of hypoplastic left heart [18,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation